Aromatic hydrocarbon adsorbent for simulated moving bed as well as preparation method and application of aromatic hydrocarbon adsorbent

By modifying the molecular sieve raw powder, an aromatic adsorbent was prepared for simulated mobile beds, which solved the problems of low purity of aromatic components and low target product yield in the prior art, and achieved efficient aromatic adsorption and separation, with product purity reaching more than 99%.

CN119608129AActive Publication Date: 2025-03-14NANJING CMEC PETROCHEMICAL ENG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411753288.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

In the existing aromatic hydrocarbon adsorption and separation technology, the aromatic hydrocarbon component product purity is low and the target product yield is low, which leads to the aromatic hydrocarbon component being used through further purification processes, which increases the treatment cost.

Method used

By modifying the molecular sieve raw powder, an aromatic adsorbent is prepared for simulating a mobile bed. The modification step includes ion-substitution modification of the molecular sieve using a modifier, adjusting its surface properties and structure, and improving the selective adsorption capacity of aromatic hydrocarbons. At the same time, the uniformity of the adsorbent particles and the appropriate particle size range are ensured through the seeding and long ball steps, and the moisture and organic matter are removed through the drying and calcining steps to improve the stability of the adsorbent.

Benefits of technology

The selective adsorption capacity and stability of aromatic adsorbents are improved, the adsorption efficiency of aromatic hydrocarbons is enhanced, the bed pressure drop is reduced, and the purity of aromatic component products is improved to more than 99%, reducing the need for subsequent purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165534140000121
    Figure BDA0005165534140000121
  • Figure BDA0005165534140000131
    Figure BDA0005165534140000131
Patent Text Reader

Abstract

The invention provides an aromatic hydrocarbon adsorbent for a simulated moving bed and a preparation method of the aromatic hydrocarbon adsorbent, and relates to the technical field of aromatic hydrocarbon adsorbents. The preparation method comprises the following steps: modifying molecular sieve raw powder by using a modifier to obtain modified raw powder; preparing seed balls by utilizing the modified raw powder; growing the seed balls and the modified raw powder to obtain small granular balls with the particle size of 0.5-1.5 mm; and drying and roasting the small granular balls to obtain the aromatic hydrocarbon adsorbent. The aromatic hydrocarbon adsorbent is prepared by the preparation method. The prepared aromatic hydrocarbon adsorbent has high selective adsorption capacity on aromatic hydrocarbon and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of aromatic hydrocarbon adsorbents, and in particular to an aromatic hydrocarbon adsorbent for a simulated moving bed and a preparation method and application thereof. Background Art

[0002] Under the dual pressure of my country's economic slowdown and the rapid development of alternative energy, the growth rate of refined oil demand has slowed down, diesel consumption has basically reached its peak, and gasoline consumption is expected to reach its peak around 2025. Unlike the refined oil market, basic chemicals such as olefins and aromatics are in strong demand, and domestic production capacity is insufficient, so a large amount of imports are still required. If the components in diesel can be separated to obtain high-purity straight-chain alkanes, cycloalkanes, isoalkanes and aromatics, high-purity aromatics can be used as high-quality aromatic solvents or high-quality BTX (benzene, toluene, xylene) production increase raw materials, which not only realizes the classified management of gasoline and diesel components, and provides raw materials for efficient conversion and accurate processing of gasoline and diesel, but also reduces the diesel-to-gasoline ratio of refineries, and improves the economic and social benefits of enterprises.

[0003] In industry, the main separation technologies for mixed aromatic components of oil products include precision distillation, membrane separation technology, adsorption separation technology, etc. Precision distillation uses the difference in boiling points of each component to achieve separation and purification, but its separation fraction is narrow, the process is complex, and the operation is difficult. Membrane separation technology mainly uses the difference in diffusion coefficients of different components when passing through the membrane to separate mixed components. Although it has the advantages of low energy consumption and simple process, the preparation of separation membranes is relatively complex and costly, and it is difficult to achieve a balance between high flux and high selectivity, which restricts its industrial application. The main methods of adsorption separation technology are fixed bed and simulated moving bed adsorption separation. Compared with precision distillation and membrane separation technology, adsorption separation technology has the advantages of higher product recovery rate and purity, lower energy consumption, long adsorbent life, and stable operation.

[0004] However, most of the current adsorption separation technologies have problems such as low purity of aromatic component products and low yield of target products, which means that the aromatic components must undergo further purification processes before they can be used, increasing processing costs. Summary of the invention

[0005] In order to improve the problems of low purity of aromatic component products and low yield of target products in the current aromatic adsorption separation technology, the present application provides an aromatic adsorbent for a simulated moving bed and a preparation method and application thereof.

[0006] In a first aspect, the present application provides a method for preparing an aromatic hydrocarbon adsorbent for a simulated moving bed, using the following technical solution: A method for preparing an aromatic hydrocarbon adsorbent for simulating a moving bed comprises the following steps: Step S1: using a modifier to modify the molecular sieve raw powder to obtain modified raw powder; Step S2: preparing bulbs using the modified raw powder; Step S3: using the seed balls and the modified raw powder to grow balls, so that the seed balls grow into small granular balls with a particle size of 0.5 to 1.5 mm; Step S4: drying and roasting the pellets to obtain the aromatic hydrocarbon adsorbent.

[0007] The present application ensures that the adsorbent has excellent adsorption performance and stability by modifying the original molecular sieve powder. The modification step improves its selective adsorption capacity for aromatic hydrocarbons by adjusting the surface properties and structure of the molecular sieve. The seeding and balling steps ensure the uniformity of the adsorbent particles and the appropriate particle size range, which helps to improve the adsorption efficiency and reduce the bed pressure drop. The drying and roasting steps further remove moisture and organic matter from the adsorbent, stabilize its structure, and improve thermal and chemical stability.

[0008] Optionally, the modified raw powder includes molecular sieve raw powder, a pore expanding agent and a binder, the weight ratio of the molecular sieve raw powder to the pore expanding agent is 88-92:8-12, and the weight of the binder is 4%-6% of the sum of the weights of the molecular sieve raw powder and the pore expanding agent.

[0009] Furthermore, the modified raw powder includes molecular sieve raw powder, a pore expander and a binder, the dry weight ratio of the molecular sieve raw powder and the pore expander after high-temperature calcination is 88-92:8-12, and the weight of the binder is 4%-6% of the sum of the dry weights of the molecular sieve raw powder and the pore expander after high-temperature calcination.

[0010] The present application further defines the raw material composition of the modified original powder. By adding a pore expander and a binder and mixing them with the molecular sieve original powder, the structure and performance of the adsorbent can be optimized; the pore expander helps to increase the porosity and improve the pore structure, thereby increasing the adsorption capacity and diffusion rate; the binder helps to form and stabilize the particles, preventing the particles from breaking and agglomerating during the preparation and use process.

[0011] Optionally, the specific operations of step S1 are as follows: The molecular sieve raw powder, the pore expanding agent, the binder and water are mixed to form a slurry with a solid content of 30% to 50%, and the pH value of the slurry is adjusted to 3 to 5, and stirred evenly; The slurry is heated to 90-100° C., a modifier solution is added, and the slurry is kept at the temperature for 2-4 hours to obtain a modified material; The modified material is dehydrated and dried, and the dried material is crushed to less than 200 meshes to obtain the modified raw powder.

[0012] The present application forms a slurry by mixing molecular sieve raw powder, pore expander, binder and water, and adjusting the pH value to ensure uniform distribution and interaction between the components. After heating and adding the modifier solution, the modifier can fully combine with the active sites on the surface of the molecular sieve raw powder to form new chemical bonds or change the chemical properties of the surface, thereby improving its adsorption capacity for aromatic hydrocarbons.

[0013] The present application helps to form stronger chemical bonds between the modifier molecules and the active sites on the surface of the molecular sieve raw powder by adjusting the pH value of the slurry before modification. The formation of these chemical bonds can enhance the binding force between the molecular sieve particles, thereby improving the overall strength of the product and reducing the wear of the molecular sieve during use.

[0014] Optionally, the molecular sieve raw powder has a silicon-aluminum ratio of 2.2-6.0, and a static saturated water absorption of greater than 32% under the conditions of a temperature of 25° C. and a humidity of 75%; The binder is alumina or kaolin; The pore-enlarging agent is polyvinyl alcohol, sesbania powder or starch.

[0015] The present application helps to ensure the adsorption capacity and stability of the molecular sieve raw powder by limiting the silicon-aluminum ratio and the static saturated water absorption of the molecular sieve raw powder. The selection of the binder and the pore-enlarging agent can optimize the structure and performance of the adsorbent.

[0016] Optionally, the modifier solution is an aqueous solution of calcium salt, magnesium salt or barium salt, and the mass concentration of the modifier solvent is 10% to 20%; The amount of the modifier solution added is 1.875-2 times the weight of the original molecular sieve powder.

[0017] The present application utilizes a modifier to perform ion replacement modification on the original molecular sieve powder, so that the sodium ions in the original molecular sieve powder are replaced by the divalent metal ions (calcium ions, magnesium ions or barium ions) of the modifier. Since the valence state of the replaced ions is higher than that of the sodium ions, the interaction between them and the oxygen atoms in the molecular sieve framework is stronger, thereby enhancing the structural stability of the molecular sieve, helping the molecular sieve to maintain its shape and pore structure during the adsorption process, and preventing structural collapse caused by pressure or temperature changes during the adsorption process.

[0018] Moreover, after sodium ions are replaced by divalent ions, the charge distribution of the molecular sieve changes. The substituted ions carry more positive charges, which increases the charge density on the surface of the molecular sieve and enhances the polarity, which helps the interaction between the molecular sieve and the aromatic molecules. Aromatic molecules are usually polar, so they are more easily adsorbed by molecular sieves with enhanced polarity. The enhanced polarity also helps to increase the adsorption rate of aromatics by molecular sieves. Aromatic molecules are more easily attracted to the surface of the molecular sieve and enter its pores more quickly for adsorption.

[0019] Optionally, the specific operation of step S2 is as follows: putting the modified raw powder into a sugar coating pan, rotating the pan, and spraying water into the sugar coating pan at the same time, so that the modified raw powder is gradually formed into round particles under the conditions of continuous rotation and water spraying, and then stopping the rotation, taking out the granular material in the pan, and sieving out 0.2-0.5 mm particles as seed balls.

[0020] The present application can gradually shape the modified raw powder into round particles by rotating and spraying water in the sugar coating pan. By controlling the amount of water sprayed and the rotation speed, uniform and regular balls can be prepared. The particle size and shape of the balls directly affect the particle size distribution and bed pressure drop of the final adsorbent.

[0021] Optionally, the specific operation of step S3 is as follows: put the bulbs into the sugar coating pot again, rotate the pot, and continuously spray water and the modified raw powder into the sugar coating pot to make the bulb particles gradually grow. When the particle size grows to 1.5 mm, stop growing the bulbs, take out the particles in the pot, and sieve out the particles of 0.5 to 1.5 mm.

[0022] The present application can make the seed ball particles gradually grow to the required particle size range by continuously spraying water and spraying modified raw powder. This step ensures the uniformity and suitable particle size range of the adsorbent particles, which helps to improve the adsorption efficiency and reduce the bed pressure drop. At the same time, by accurately controlling the amount of water sprayed and the amount of modified raw powder added, the particle size can be accurately controlled, thereby obtaining adsorbent particles that meet the requirements.

[0023] Optionally, the temperature of the drying treatment in step S4 is 120-150° C., and the drying time is 2-4 hours.

[0024] Optionally, the calcination treatment in step S4 is carried out in a stepwise heating manner, and the pellets are kept at 180-200°C, 280-300°C, 380-400°C, and 550-600°C for 1-2 hours respectively.

[0025] The present application can remove moisture and organic matter in the adsorbent by using a calcination process. The step-wise heating method helps to avoid structural damage and performance degradation caused by a sharp temperature increase, and can further improve the adsorption performance and stability of the adsorbent.

[0026] In a second aspect, the present application provides an aromatic hydrocarbon adsorbent prepared by the above-mentioned preparation method.

[0027] The aromatic hydrocarbon adsorbent prepared in the present application has high selective adsorption capacity for aromatic hydrocarbons and good stability.

[0028] In a third aspect, the present application provides an application of an aromatic adsorbent, wherein the aromatic adsorbent is applied to a simulated moving bed to adsorb and separate aromatics in a mixed oil product.

[0029] When the above-mentioned aromatic adsorbent is used in the present application for the adsorption and separation of aromatics, various aromatics in the mixed oil can be adsorbed, thereby separating the aromatics from the mixed oil, and the purity of the aromatics in the obtained aromatic component product reaches more than 99%, which can be directly applied to downstream production.

[0030] In summary, the present application includes at least one of the following beneficial effects: 1. This application ensures that the adsorbent has excellent adsorption performance and stability by modifying the original molecular sieve powder. The modification step improves its selective adsorption capacity for aromatic hydrocarbons by adjusting the surface properties and structure of the molecular sieve. The seeding and balling steps ensure the uniformity of the adsorbent particles and the appropriate particle size range, which helps to improve the adsorption efficiency and reduce the bed pressure drop. The drying and roasting steps further remove moisture and organic matter from the adsorbent, stabilize its structure, and improve thermal and chemical stability.

[0031] 2. The aromatic hydrocarbon adsorbent prepared in the present application has high selective adsorption capacity for aromatic hydrocarbons and good stability.

[0032] 3. When the above-mentioned aromatic adsorbent is used for the adsorption and separation of aromatics, the present application can adsorb various aromatics in the mixed oil products, thereby separating the aromatics from the mixed oil products, and the purity of the aromatics in the obtained aromatic component products reaches more than 99%, which can be directly applied to downstream production. DETAILED DESCRIPTION

[0033] Example 1 Example 1 provides an aromatic hydrocarbon adsorbent, which is as follows: (1) Prepare raw materials. Select 13X molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 2.4, a static saturated water absorption of 33wt% at a temperature of 25°C and a humidity of 75%, and a 25% ignition loss at 600°C. Select alumina powder as the binder, with a specific surface area of ​​250g / m 2 , pore volume 0.5 ml / g, ignition reduction 35% at 600℃. Polyvinyl alcohol with 100% purity is selected as the pore expander. The dosage of the three raw materials is 100 kg of 13X molecular sieve powder, 15.8 kg of alumina powder, and 3.42 kg of polyvinyl alcohol. The dry weights of the first two powders after calcination at 600℃ are 75 kg and 10.27 kg respectively. Therefore, the dry weight ratio of 13X molecular sieve powder, alumina powder, and polyvinyl alcohol is 88:12:4.

[0034] (2) Add 200 liters of deionized water to the reactor, start stirring, and add three raw materials in the order of polyvinyl alcohol, alumina powder, and 13X molecular sieve raw powder. After the three materials are added, use nitric acid to adjust the pH value of the slurry to 4, and stir at a speed of 100 rpm for 30 minutes; then heat the materials in the reactor to 95°C, add 150 kg of the prepared 10wt% calcium chloride solution, and keep the temperature at 95°C for 4 hours to obtain the modified material; put the modified material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 150°C, keep the temperature for 4 hours, take out the material and send it to a pulverizer for pulverization. The particle size is greater than 200 mesh and bagged to obtain the modified raw powder.

[0035] (3) Weigh 20 kg of modified raw powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0036] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 meters again for ball growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the modified raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the ball growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0037] (5) The above-mentioned 0.5-1.5 mm granular balls are placed in a tray and put into an oven for drying at a drying temperature of 140°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 580°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0038] Example 2 Example 2 provides an aromatic hydrocarbon adsorbent, which is as follows: (1) Prepare raw materials. Select 13X molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 2.3, a static saturated water absorption of 33wt% at a temperature of 25°C and a humidity of 75%, and a ignition loss of 22% at 600°C. Select alumina powder as the binder, with a specific surface area of ​​260g / m 2, pore volume is 0.58ml / g, burning reduction is 35% at 600℃. Polyvinyl alcohol with 100% purity is selected as the pore expanding agent. The dosage of the three raw materials is 100 kg of 13X molecular sieve powder, 13.3 kg of alumina powder, and 4.32 kg of polyvinyl alcohol. The dry weights of the first two powders after burning at 600℃ are 78 kg and 8.645 kg respectively. Therefore, the dry weight ratio of 13X molecular sieve powder, alumina powder, and polyvinyl alcohol is 90:10:5.

[0039] (2) Add 200 liters of deionized water to the reactor, start stirring, and add three raw materials in the order of polyvinyl alcohol, alumina powder, and 13X molecular sieve raw powder. After the three materials are added, use nitric acid to adjust the pH value of the slurry to 5, and stir at a speed of 100 rpm for 30 minutes; then heat the materials in the reactor to 95°C, add 150 kg of the prepared 15wt% magnesium chloride solution, and maintain the temperature at 95°C for 4 hours to obtain the modified material; put the modified material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 150°C, the temperature is maintained for 4 hours, and the material is taken out and sent to a pulverizer for pulverization. The particle size is greater than 200 mesh and bagged to obtain the modified raw powder.

[0040] (3) Weigh 20 kg of modified raw powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0041] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 meters again for ball growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the modified raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the ball growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0042] (5) The above-mentioned 0.5-1.5 mm granular balls are placed on a plate and put into an oven for drying at a drying temperature of 140°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 590°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0043] Example 3 Example 3 provides an aromatic hydrocarbon adsorbent, which is as follows: (1) Prepare the raw materials. Select 13X molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 2.5, a static saturated water absorption of 33wt% at a temperature of 25°C and a humidity of 75%, and a 23% reduction at 600°C. Select kaolin powder as the binder, which has a 39% reduction at 600°C. Select polyvinyl alcohol with a purity of 100% as the pore expander. The amounts of the three raw materials are 100 kg of 13X molecular sieve raw powder, 11 kg of kaolin powder, and 4.19 kg of polyvinyl alcohol. The dry weights of the first two powders after calcination at 600°C are 77 kg and 6.71 kg, respectively. Therefore, the dry weight ratio of 13X molecular sieve raw powder, alumina powder, and polyvinyl alcohol is 92:8:5.

[0044] (2) Add 200 liters of deionized water to the reactor, start stirring, and add three raw materials in the order of polyvinyl alcohol, kaolin powder, and 13X molecular sieve raw powder. After the three materials are added, use nitric acid to adjust the pH value of the slurry to 3, and stir at a speed of 100 rpm for 30 minutes; then raise the temperature of the materials in the reactor to 95°C, add 150 kg of the prepared 15wt% magnesium chloride solution, and maintain the temperature at 95°C for 4 hours to obtain the modified material; put the modified material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 150°C, the temperature is maintained for 4 hours, and the material is taken out and sent to a pulverizer for pulverization. The particle size is greater than 200 mesh and bagged to obtain the modified raw powder.

[0045] (3) Weigh 20 kg of modified raw powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0046] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 meters again for ball growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the modified raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the ball growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0047] (5) The above-mentioned 0.5-1.5 mm granular balls are placed on a plate and put into an oven for drying at a drying temperature of 140°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 600°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0048] Example 4 Example 4 provides an aromatic hydrocarbon adsorbent, which is as follows: (1) Prepare the raw materials. Select 13X molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 2.5, a static saturated water absorption of 34wt% at a temperature of 25°C and a humidity of 75%, and a 23% reduction at 600°C. Select kaolin powder as the binder, which has a 39% reduction at 600°C. Select polyvinyl alcohol with a purity of 100% as the pore expander. The amounts of the three raw materials are 100 kg of 13X molecular sieve raw powder, 12.5 kg of kaolin powder, and 3.38 kg of polyvinyl alcohol. The dry weights of the first two powders after calcination at 600°C are 77 kg and 7.625 kg, respectively. Therefore, the dry weight ratio of 13X molecular sieve raw powder, alumina powder, and polyvinyl alcohol is 91:9:4.

[0049] (2) Add 200 liters of deionized water to the reactor, start stirring, and add three raw materials in the order of polyvinyl alcohol, kaolin powder, and 13X molecular sieve raw powder. After the three materials are added, use nitric acid to adjust the pH value of the slurry to 4, and stir at a speed of 110 rpm for 30 minutes; then heat the materials in the reactor to 94° C., add 150 kg of the prepared 15wt% barium chloride solution, and keep the temperature at 94° C. for 4 hours to obtain the modified material; put the modified material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 140° C., keep the temperature for 4 hours, take out the material and send it to a pulverizer for pulverization. The particle size is greater than 200 mesh, and the material is bagged to obtain the modified raw powder.

[0050] (3) Weigh 20 kg of modified raw powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0051] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 meters again for ball growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the modified raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the ball growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0052] (5) The above-mentioned 0.5-1.5 mm granular balls are placed on a plate and put into an oven for drying at a drying temperature of 150°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 600°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0053] Example 5 Example 5 provides an aromatic hydrocarbon adsorbent, which is as follows: (1) Prepare the raw materials. Select 13X molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 2.3, a static saturated water absorption of 34wt% at a temperature of 25°C and a humidity of 75%, and a 23% reduction at 600°C. Select kaolin powder as a binder, which reduces by 39% at 600°C. Select starch as a pore expander. The amounts of the three raw materials are 100 kg of 13X molecular sieve raw powder, 12.5 kg of kaolin powder, and 5.07 kg of starch (weight after high-temperature calcination). The dry weights of the first two powders after calcination at 600°C are 77 kg and 7.625 kg, respectively. Therefore, the dry weight ratio of 13X molecular sieve raw powder, alumina powder, and starch is 91:9:6.

[0054] (2) Add 200 liters of deionized water to the reactor, start stirring, and add the three raw materials in the order of starch, kaolin powder, and 13X molecular sieve raw powder. After the three materials are added, use nitric acid to adjust the pH value of the slurry to 4, and stir at a speed of 110 rpm for 30 minutes; then heat the materials in the reactor to 93°C, add 150 kg of the prepared 13wt% calcium chloride solution, and keep the temperature at 93°C for 4 hours to obtain the modified material; put the modified material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 130°C, keep the temperature for 4 hours, take out the material and send it to a pulverizer for pulverization. The particle size is greater than 200 mesh and bagged to obtain the modified raw powder.

[0055] (3) Weigh 20 kg of modified raw powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0056] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 meters again for ball growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the modified raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the ball growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0057] (5) The above-mentioned 0.5-1.5 mm granular balls are placed on a plate and put into an oven for drying at a drying temperature of 150°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 590°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0058] Example 6 Example 6 provides an aromatic hydrocarbon adsorbent, which is as follows: 1) Prepare the raw materials. Select NaY molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 5.5, a static saturated water absorption of 32wt% at a temperature of 25°C and a humidity of 75%, and a 20% reduction at 600°C. Select kaolin powder as a binder, which reduces by 39% at 600°C. Select sesbania powder as a pore expander. The amounts of the three raw materials are 100 kg of NaY molecular sieve raw powder, 17.9 kg of kaolin powder, and 3.63 kg of sesbania powder (weight after high-temperature calcination). The dry weights of the first two powders after calcination at 600°C are 80 kg and 10.919 kg, respectively. Therefore, the dry weight ratio of 13X molecular sieve raw powder, alumina powder, and sesbania powder is 88:12:4.

[0059] (2) Add 200 liters of deionized water to the reactor, start stirring, and add the three raw materials in the order of sesbania powder, kaolin powder, and NaY molecular sieve raw powder. After the three materials are added, use nitric acid to adjust the pH value of the slurry to 4, and stir at a speed of 110 rpm for 30 minutes; then heat the materials in the reactor to 95°C, add 150 kg of the prepared 13wt% calcium chloride solution, and keep the temperature at 95°C for 4 hours to obtain the modified material; put the modified material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 130°C, keep the temperature for 4 hours, take out the material and send it to a crusher for crushing. The particle size is greater than 200 mesh, and the modified raw powder is obtained.

[0060] (3) Weigh 20 kg of modified raw powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0061] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 meters again for ball growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the modified raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the ball growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0062] (5) The above-mentioned 0.5-1.5 mm granular balls are placed on a plate and put into an oven for drying at a drying temperature of 130°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 580°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0063] Example 7 Example 7 provides an aromatic hydrocarbon adsorbent, which is as follows: 1) Prepare the raw materials. Select NaY molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 5.2, a static saturated water absorption of 33wt% at a temperature of 25°C and a humidity of 75%, and a 20% reduction at 600°C. Select kaolin powder as a binder, which reduces by 39% at 600°C. Select polyvinyl alcohol with a purity of 100% as a pore expander. The amounts of the three raw materials are 100 kg of NaY molecular sieve raw powder, 11.4 kg of kaolin powder, and 3.48 kg of polyvinyl alcohol. The dry weights of the first two powders after calcination at 600°C are 80 kg and 6.954 kg, respectively. Therefore, the dry weight ratio of 13X molecular sieve raw powder, alumina powder, and polyvinyl alcohol is 92:8:4.

[0064] (2) Add 200 liters of deionized water to the reactor, start stirring, and add three raw materials in the order of polyvinyl alcohol, kaolin powder, and NaY molecular sieve raw powder. After the three materials are added, use nitric acid to adjust the pH value of the slurry to 4, and stir at a speed of 100 rpm for 30 minutes; then raise the temperature of the materials in the reactor to 92°C, add 150 kg of the prepared 18wt% calcium chloride solution, and maintain the temperature at 92°C for 4 hours to obtain the modified material; put the modified material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 130°C, the temperature is maintained for 4 hours, and the material is taken out and sent to a pulverizer for pulverization. The particle size is greater than 200 mesh and bagged to obtain the modified raw powder.

[0065] (3) Weigh 20 kg of modified raw powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0066] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 meters again for ball growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the modified raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the ball growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0067] (5) The above-mentioned 0.5-1.5 mm granular balls are placed on a plate and put into an oven for drying at a drying temperature of 130°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 560°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0068] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that the molecular sieve raw powder that is not modified by a modifier is used for preparation. The specific steps of Comparative Example 1 are as follows: (1) Prepare raw materials. Select 13X molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 2.4, a static saturated water absorption of 33wt% at a temperature of 25°C and a humidity of 75%, and a 25% ignition loss at 600°C. Select alumina powder as the binder, with a specific surface area of ​​250g / m 2, pore volume 0.5 ml / g, ignition reduction 35% at 600℃. Polyvinyl alcohol with 100% purity is selected as the pore expander. The dosage of the three raw materials is 100 kg of 13X molecular sieve powder, 15.8 kg of alumina powder, and 3.42 kg of polyvinyl alcohol. The dry weights of the first two powders after calcination at 600℃ are 75 kg and 10.27 kg respectively. Therefore, the dry weight ratio of 13X molecular sieve powder, alumina powder, and polyvinyl alcohol is 88:12:4.

[0069] (2) Add 200 liters of deionized water into the reaction kettle, start stirring, and add three raw materials in the order of polyvinyl alcohol, alumina powder, and 13X molecular sieve raw powder. After the three materials are added, stir at a speed of 100 rpm for 30 minutes to obtain a mixed material; put the mixed material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 150° C., the temperature is maintained for 4 hours, and the material is taken out and sent to a pulverizer for pulverization. The particle size is greater than 200 mesh, and the material is bagged to obtain the raw powder.

[0070] (3) Weigh 20 kg of the original powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0071] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 m again for growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the bulb growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0072] (5) The above-mentioned 0.5-1.5 mm granular balls are placed in a tray and put into an oven for drying at a drying temperature of 140°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 580°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0073] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that no pore-enlarging agent is added during the modification of the molecular sieve raw powder. The specific steps of Comparative Example 2 are as follows: (1) Prepare raw materials. Select 13X molecular sieve raw powder as the molecular sieve raw powder, with a silicon-aluminum ratio of 2.4, a static saturated water absorption of 33wt% at a temperature of 25°C and a humidity of 75%, and a 25% ignition loss at 600°C. Select alumina powder as the binder, with a specific surface area of ​​250g / m 2 , pore volume 0.5 ml / g, ignition reduction 35% at 600°C. The dosage of the two raw materials is 100 kg of 13X molecular sieve powder and 15.8 kg of alumina powder. The dry weights of the two powders after calcination at 600°C are 75 kg and 10.27 kg respectively. Therefore, the dry weight ratio of 13X molecular sieve powder and alumina powder is 88:12.

[0074] (2) Add 200 liters of deionized water to the reactor, start stirring, and add the two raw materials in the order of alumina powder and 13X molecular sieve raw powder. After the two materials are added, use nitric acid to adjust the pH value of the slurry to 4, and stir at a speed of 100 rpm for 30 minutes; then heat the materials in the reactor to 95°C, add 150 kg of the prepared 10wt% calcium chloride solution, and keep the temperature at 95°C for 4 hours to obtain the modified material; put the modified material into a centrifuge for dehydration, and the cake-like material after water removal is placed on a plate and put into an oven. After the temperature is raised to 150°C, keep the temperature for 4 hours, take out the material and send it to a pulverizer for pulverization. The particle size is greater than 200 mesh and bagged to obtain the modified raw powder.

[0075] (3) Weigh 20 kg of modified raw powder and pour it into a sugar coating pan with a diameter of 1 meter. Rotate the pan and keep the speed at 20 rpm. Spray deionized water into the pan continuously. The powder gradually forms into round particles under the conditions of continuous rotation and water spraying. After rotating for 30 minutes, stop rotating, take out the granular material in the pan, sieve it, and select the particles of 0.2-0.5 mm as seed balls.

[0076] (4) The bulbs are placed in a sugar coating pot with a diameter of 1.2 meters again for ball growth. The sugar coating pot is started and the rotation speed is maintained at 30 rpm. At the same time, water and the modified raw powder obtained above are continuously sprayed into the sugar coating pot. The material humidity is controlled to ensure that the particles roll smoothly in the pot. After such repeated addition of water and powder, the bulb particles gradually grow. When the particle size grows to 1.5 mm, the ball growth is stopped, the particles in the pot are taken out, and the particles of 0.5 to 1.5 mm are sieved.

[0077] (5) The above-mentioned 0.5-1.5 mm granular balls are placed in a tray and put into an oven for drying at a drying temperature of 140°C. After 4 hours, they are put into a converter for roasting. The temperatures at various points in the converter are controlled at 200°C, 300°C, 400°C, and 580°C. The residence time at each point is 1 hour. After the roasting is completed, the material is unloaded and sealed while hot as a finished product for standby use.

[0078] Performance Testing An oil product rich in mixed aromatics is prepared as an adsorption raw material, wherein the main substances are: normal alkanes, isoalkanes, cycloalkanes and mixed aromatics (benzene, toluene, meta-xylene), wherein the aromatic content is 25.3%.

[0079] The adsorbent is loaded into a simulated moving bed, and the aromatic adsorption separation is a countercurrent simulated moving bed adsorption separation process. The adsorption bed has 12 layers, the adsorption separation temperature is 120°C, the pressure is 1MPa, and the desorbent is 98.8% pure diethylbenzene. Two streams of material are extracted from the simulated moving bed, one of which is an extract rich in aromatic components, and the other is a residual liquid rich in non-aromatic components. The extract is sampled and analyzed. The analysis items include aromatic purity, aromatic recovery rate, aromatic adsorption capacity, adsorbent bulk density and attrition. Among them, the adsorbent bulk density is obtained according to the GB / T6286-2021 molecular sieve bulk density determination method; the attrition is obtained according to the GB / T10505.2-1989 3A molecular sieve attrition rate determination method. The aromatic purity, aromatic recovery rate and aromatic adsorption capacity can be obtained by the following calculation method, and the specific results are shown in Table 1.

[0080] Aromatic purity = mass of aromatics in the extract / total mass of the extract × 100%; Aromatic hydrocarbon recovery rate = mass of aromatic hydrocarbons in the extract / mass of total aromatic hydrocarbons in the feed raw material × 100%; Aromatic hydrocarbon adsorption capacity = weight of aromatic hydrocarbons in the adsorbent / weight of the adsorbent × 100%.

[0081] Table 1 Analysis results of various embodiments and comparative examples From the results in Table 1, it can be seen that the aromatic adsorbent prepared in Examples 1-7 is highly selective for aromatics in the mixed oil, so that almost all of the aromatics in the mixed oil are extracted into the extract, and more than 99% of the obtained extract is aromatics, which can be used directly without further processing; moreover, the aromatic adsorbent obtained in Examples 1-7 also has a higher adsorption capacity and lower abrasion.

[0082] Compared with Comparative Example 1, the aromatic hydrocarbon adsorbent obtained in Example 1 has higher aromatic hydrocarbon selectivity and higher aromatic hydrocarbon adsorption capacity due to the modification by calcium chloride; compared with Comparative Example 2, the aromatic hydrocarbon adsorbent obtained in Example 1 has higher aromatic hydrocarbon adsorption selectivity and adsorption capacity due to the addition of a pore expanding agent during the modification process.

[0083] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing an aromatic hydrocarbon adsorbent for a simulated moving bed, characterized in that: The steps include: Step S1: using a modifier to modify the molecular sieve raw powder to obtain modified raw powder; Step S2: preparing bulbs using the modified raw powder; Step S3: using the seed balls and the modified raw powder to grow balls, so that the seed balls grow into small granular balls with a particle size of 0.5 to 1.5 mm; Step S4: drying and roasting the pellets to obtain the aromatic hydrocarbon adsorbent.

2. The method for preparing an aromatic hydrocarbon adsorbent according to claim 1, characterized in that: The modified raw powder includes molecular sieve raw powder, a pore expander and a binder. The weight ratio of the molecular sieve raw powder to the pore expander is 88-92:8-12. The weight of the binder is 4%-6% of the sum of the weights of the molecular sieve raw powder and the pore expander.

3. The method for preparing an aromatic hydrocarbon adsorbent according to claim 2, characterized in that: The specific operation of step S1 is as follows: The molecular sieve raw powder, the pore expanding agent, the binder and water are mixed to form a slurry with a solid content of 30% to 50%, and the pH value of the slurry is adjusted to 3 to 5, and stirred evenly; The slurry is heated to 90-100° C., a modifier solution is added, and the slurry is kept at the temperature for 2-4 hours to obtain a modified material; The modified material is dehydrated and dried, and the dried material is crushed to less than 200 meshes to obtain the modified raw powder.

4. The method for preparing an aromatic hydrocarbon adsorbent according to claim 3, characterized in that: The molecular sieve raw powder has a silicon-aluminum ratio of 2.2-6.0, and a static saturated water absorption of more than 32% at a temperature of 25°C and a humidity of 75%; The binder is alumina or kaolin; The pore-enlarging agent is polyvinyl alcohol, sesbania powder or starch.

5. The method for preparing an aromatic hydrocarbon adsorbent according to claim 4, characterized in that: The modifier solution is an aqueous solution of calcium salt, magnesium salt or barium salt, and the mass concentration of the modifier solvent is 10% to 20%; The amount of the modifier solution added is 1.875-2 times the weight of the original molecular sieve powder.

6. The method for preparing an aromatic hydrocarbon adsorbent according to claim 1, characterized in that: The specific operation of step S2 is as follows: put the modified raw powder into the sugar coating pot, rotate the pot body, and spray water into the sugar coating pot at the same time, so that the modified raw powder is gradually formed into round particles under the conditions of continuous rotation and water spraying, and then stop rotating, take out the granular material in the pot, and sieve out 0.2-0.5mm particles as seed balls.

7. The method for preparing an aromatic hydrocarbon adsorbent according to claim 1, characterized in that: The specific operation of step S3 is as follows: put the ball into the sugar coating pot again, rotate the pot, and continuously spray water and the modified raw powder into the sugar coating pot to make the ball particles gradually grow. When the particle size grows to 1.5 mm, stop growing the ball, take out the particles in the pot, and sieve out the particles of 0.5~1.5 mm.

8. The method for preparing an aromatic hydrocarbon adsorbent according to claim 1, characterized in that: The calcination treatment in step S4 is carried out in a step-by-step heating manner, and the pellets are kept at 180-200°C, 280-300°C, 380-400°C, and 550-600°C for 1-2 hours respectively.

9. An aromatic hydrocarbon adsorbent prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the aromatic hydrocarbon adsorbent according to claim 9, characterized in that: The aromatic hydrocarbon adsorbent is applied to a simulated moving bed to adsorb and separate aromatic hydrocarbons in mixed oil products.

Citation Information

Patent Citations

  • Preparation method of molecular sieve adsorbent

    CN102049246A

  • Inferior-diesel hydro-upgrading catalyst carrier and preparation method thereof

    CN107233913A

  • Flame-retardant hydrophobic porous adsorbent as well as preparation method and application thereof

    CN114713183A

  • MFI zeolite adsorbent containing hierarchical pores as well as preparation method and application of MFI zeolite adsorbent

    CN116510685A

  • Preparation method of acid modified calcium-based CO2 adsorbent pellets

    CN118122265A